Nasz profesor Sylwester Dworacki - Danielewicz, Jerzy (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The author presents the profile and scholarly achievements of Professor Sylwester Dworacki, a distinguished classicist from the University of Poznań, to celebrate his 70th birthday.